KELAYAKAN FINANSIAL DAN FAKTOR PRODUKSI PADI SAWAH DI DESA SUKARAMI KECAMATAN AIR NIPIS KABUPATEN BENGKULU SELATAN - Sarina (University of Prof. Dr. Hazairin, SH, 2024)
Sukarami Village, Air Nipis District is one of the sub-districts in South Bengkulu district as a rice-producing area with a planting area of 326 ha consisting of 15 farmer groups. Farming paddy rice is done from generation to generation. The research objective was to determine the feasibility and to determine the factors that influence lowland rice farming in the village of Sukarami, Air Nipis District, South Bengkulu Regency. The research was carried out from May to September 2021 in Sukarami Village, Air Nipis District, South Bengkulu Regency. The location selection was carried out purposively with the consideration that all the inhabitants of Sukarami Village grow rice. The data analyzed are production costs, revenues, income, R/C ratio, cost of goods, and factors affecting rice farming. The results of the study show that the average land area is 0.75 ha, the average income is IDR 14,19,842 / farming, the average production cost of Rp. 6,027,215.20/farm, average income of IDR 8,892.62680/farm. R/C 2,475. Basic Price Rp. IDR 3,635.75/kg. Factors of land area, seeds, fertilizers, labor and medicines have a positive effect on the production of lowland rice farming in Sukarame Village, Air Nipis District, South Bengkulu Regency.